France in 1940 in British Eyes - Richard Carswell (Revue Française de Civilisation Britannique, 2022)
Although British views on the fall of France in 1940 were mixed, the disaster triggered a latent Francophobia which expressed itself in popular resentment at France’s military defeat and armistice with Germany. While nowadays historians generally agree on the military causes of the fall of France, British popular attitudes to France at the time of the defeat were influenced by the myths that rapidly formed around Britain’s stance in 1940. By the end of the war the British had developed a sense of superiority over continental Europeans. But they also felt guilty about Britain’s failed pre-war policy of appeasement. Questions for historians to ponder include how far this feeling of guilt covered – if at all – Britain’s lukewarm diplomatic and military support for France.